Aplikasi Pengamanan Data Gambar Dengan Menerapkan Algoritma Vigenere Chiper - Simatupang, Ayu Wandira (LPPM UNIKA Santo Thomas Medan, 2017)
The security and confidentiality of data is very important considering the rapid development of technology at this time which allows the emergence of new techniques that are misused by certain parties that can threaten security from data that are considered insignificant. Cryptography is a field of science to maintain image security. Cryptography has been implemented in many ways. The way it works is to change the original data that can be understood / read by humans (plaintext) to other forms that cannot be understood / read by humans (ciphertext). The process of transforming plaintext into chiperteks is termed encryption. While the process of returning a chipertext message to plaintext is termed decryption. Vigenere Cipher is an asymmetric cryptographic algorithm, where the key used to encrypt is different from the one used to decrypt. Vigenere Cipher is a cryptographic algorithm that uses letters and numeric values. Vigenere Cipher requires three steps in the process, namely key generation, encryption, and decryption. The process of encryption and decryption is almost the same process.